Newly developed microsatellite markers for the pan-European duck mussel, Anodonta anatina: Revisiting the main mitochondrial lineages - Lopes-Lima, Manuel (2018)
Freshwater mussels of the family Unionidae are one of the most threatened groups worldwide and have suffered severe decline over recent decades. Although the freshwater duck mussel, Anodonta anatina (Linnaeus, 1758), is still widespread, this species has shown evidence of recent declines and is already protected in some European countries. Informed conservation efforts must take into account patterns in genetic diversity and phylogeography. In the present study, 20 newly developed polymorphic loci were described and tested in seven populations of A. anatina, belonging to three previously detected divergent mtDNA lineages. The genetic diversity patterns, within and among A. anatina populations, were evaluated to test their congruence with those lineages. A high genetic differentiation (F ST ) was found among all populations, with the exception of those in Central Europe (Germany) and the UK, which were not strongly structured. The present study confirms the division of the species into three evolutionarily significant units corresponding to the three previously detected mtDNA lineages, which should be managed independently. Furthermore, owing to the high differentiation among southern European populations, the establishment of distinct management units for the Guadalquivir, Guadiana and Douro populations in the Iberian Peninsula is also proposed.